2017
DOI: 10.1063/1.4997698
|View full text |Cite
|
Sign up to set email alerts
|

Communication: Truncated non-bonded potentials can yield unphysical behavior in molecular dynamics simulations of interfaces

Abstract: Non-bonded potentials are included in most force fields and therefore widely used in classical molecular dynamics (MD) simulations of materials and interfacial phenomena. It is commonplace to truncate these potentials for computational efficiency based on the assumption that errors are negligible for reasonable cutoffs or compensated for by adjusting other interaction parameters. Arising from a metadynamics study of the wetting transition of water on a solid substrate we find that the influence of the cutoff i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 51 publications
0
6
0
Order By: Relevance
“…A direct-space cutoff of 15 Å was used for both the LJ and the Coulombic interactions and the long-range part of the Coulombic interactions was calculated using the PPPM method with a tolerance of 1 × 10 –4 in the energy. We note here that previous studies ,, have shown that the simulated contact angles obtained from MD simulations can be sensitive to the cutoff length used to truncate the LJ interactions. For this reason, we have utilized a large LJ cutoff length of 15 Å to carry out the work of adhesion simulations reported in this study.…”
Section: Theoretical Methodsmentioning
confidence: 74%
“…A direct-space cutoff of 15 Å was used for both the LJ and the Coulombic interactions and the long-range part of the Coulombic interactions was calculated using the PPPM method with a tolerance of 1 × 10 –4 in the energy. We note here that previous studies ,, have shown that the simulated contact angles obtained from MD simulations can be sensitive to the cutoff length used to truncate the LJ interactions. For this reason, we have utilized a large LJ cutoff length of 15 Å to carry out the work of adhesion simulations reported in this study.…”
Section: Theoretical Methodsmentioning
confidence: 74%
“…Additionally, we have performed independent test simulations to make sure that the topological wetting is free of the artifacts due to short cutoff distance, as previously reported. 55 In these test simulations, we increased the cutoff distance value to 25.6 Å, where the two independent sets of simulations with the mW model and with the SPC/E water model, respectively, show a water nanodroplet with ACA > 0°on a square-loop surface but in the complete-wetting state on the corresponding planar surface (Movies S12 vs S13 and S14 vs S15). Topological Wetting States.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…For bulk homogeneous systems, this is typically a sufficient approximation. However, for inhomogeneous systems such as vapor–liquid interfaces, lipid bilayers, and water droplets on solid surfaces, ignoring long-range interactions introduces artifacts. For example, Caleman et al found that surface tensions of 146 organic liquids using the GAFF and OPLS-AA force fields with an 11 Å cutoff were consistently too low compared to the experiment, with an average deviation of approximately 20% .…”
Section: Introductionmentioning
confidence: 99%